Using Laplace Transformation Technique to solve boundary value problems - Dunya Mohee Hayder (Journal of Madenat Alelem University College, 2017)
In this paper, applying Laplace transform technique will be discussed and to solve partial differential equation with boundary conditions that have significant importance in engineering and physical applications, where two kinds of partial differential equations were solved using these transformations on both sides of the equations then applying the boundary equations to find the general solutions.